Analysis of the Russian Invasion of Ukraine in Terms of Humanitarian Law - Muhammad Naufal Akbar Syaefudin; Diani Sadiawati (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2023)
This research aims to analyze the impact of Russia's invasion of Ukraine, with a specific focus on humanitarian violations and related international responses. The primary research question investigates the extent of humanitarian law breaches during the invasion and examines how the international community responds to these violations. The research adopts a field research methodology with a descriptive-qualitative approach. Data are collected through the analysis of various sources, including news reports, official documents, and interviews with experts in international relations. The analysis aims to identify humanitarian violations occurring during the conflict. Research findings indicate that Russia's invasion of Ukraine resulted in a series of humanitarian violations, including civilian casualties, forced displacements, and inhumane treatment of prisoners of war. International responses include investigations by the United Nations (UN) and the deployment of a forensic expert team by the Dutch government to gather evidence. The conclusion emphasizes the severity of Russia's invasion on global peace and underscores the importance of upholding international humanitarian law. While acknowledging Ukraine's violations as a victim, the more serious nature of Russia's actions draws sharp criticism from the international community. UN responses and diplomatic efforts highlight the crucial role of international institutions in addressing global crises. This research contributes to a deeper understanding of the impact of armed conflicts on human rights and emphasizes the necessity for collaborative global efforts to maintain world peace